Was health skepticism accounted for in communication about the COVID-19 vaccine? A content analysis of federally-sponsored public service announcements about the vaccine to protect against COVID-19 in the United States - Margaret E. Tait; Erika Franklin Fowler; Sarah E. Gollust (Preventive Medicine Reports)
Objective: To examine the content of public service announcements (PSAs) sponsored by the United States federal government to promote the COVID-19 vaccine and reveal if PSAs included content that countered health skepticism. Methods: A content analysis of televised PSAs airing from December 15th, 2020 through June 30th, 2021 in the U.S. was performed. Coders reviewed PSAs for the visual and audible appeals used to encourage vaccination, such as the opportunity vaccination provided for getting back to ‘normal’, as well as the spokespeople depicted. Messages that could mitigate health skepticism, such as content about safety and efficacy, were also coded for. Results: The first PSA aired in April of 2021, close to five months after the first person was vaccinated in the U.S. Less than 20 % (17.1 %) of PSAs explicitly encouraged vaccination and just over a quarter (25.4 %) provided details about the safety and efficacy of the vaccine. Health professionals were more commonly depicted as spokespeople in content, appearing in just under a third (29.4 %) of PSAs. Conclusions: Content that addressed and potentially reduced views of health skepticism and that may have promoted vaccine uptake, broadly, was largely absent from federally sponsored televised PSAs about the COVID-19 vaccine.